Ireland's New Traditionalists : Fianna Fáil republicanism and gender, 1926-1938 - Shonk, Kenneth L. (Book collections on Project MUSE., 2021)
"Ireland's New Traditionalists explores the efforts by Fianna Fâail in the years 1926-1938 to construct a nationalist aesthetic rooted in idealised representations of masculinity and femininity, as evident in the party's electoral ephemerae, newspapers, speeches, and film. Moreover, the book situates Fianna Fâail within the context of interwar Europe, noting especially how the party was able to navigate the anxieties and complexities of this fraught period. These efforts did much to contribute to the party's electoral successes in the 1930s that climaxed with the declaration of an independent âEire"--